Aetiology of childhood cataract in south India. Issue 7 (July 1996) - Eckstein, M.; Vijayalakshmi, P.; Killedar, M.; Gilbert, C.; Foster, A.
Abstract : AIM: To identify the causes of childhood cataract in south India with emphasis on factors that might be potentially preventable. METHODS: A total of 514 consecutive children with cataract attending an eye hospital outpatient clinic were examined and their parents interviewed by a trained interviewer using a standardised questionnaire in the local language. Serology was performed on children under 1 year of age to detect congenital rubella syndrome (CRS). Other investigations were performed as clinically indicated. RESULTS: Of the 366 children with non-traumatic cataract 25% were hereditary, 15% were due to congenital rubella syndrome, and 51% were undetermined. In children under 1 year of age 25% were due to rubella and cataract of nuclear morphology had a 75% positive predictive value for CRS. Mothers of children in the undetermined group were more likely to have taken abortifacients than a group of age matched controls (p = 0.1) but use of other medications in pregnancy was similar in both groups. Of the 148 (29%) children with traumatic cataracts three quarters were over the age of 6 years. Stick injuries were responsible for 28%, thorn injuries for 21%, and firecrackers for 5%. CONCLUSION: Nearly half of non-traumatic cataract in south India is due to potentially preventable causes (CRS and autosomal dominant disease). There is need for further work to identify the factors leading to childhood cataract in at least half of the cases for which no definite cause can as yet be determined.